Infrastructure of Authentication and Authorization for Mobile Users Using Pervasive- PKI (International Journal of Advanced Research in Computer Science, 2017)
In computer science distributed systems could be more secured with a distributed trust model based on PKI. PKI provides a frameworkto verify the identities of each entities of given domain. However, it becomes difficult to establish trust relationship across heterogeneousdomains due to different actual trust mechanism and security policy as well as the intrinsic flaw of each trust model. Network and deviceheterogeneity, nomadic mobility, intermittent connectivity and, more generally, extremely dynamic operating conditions, are major challenges inthe design of security infrastructures for pervasive computing. Yet, in a ubiquitous computing environment, limitations of traditional solutionsfor authentication and authorization can be overcome with a pervasive public key infrastructure (pervasive-PKI).Keywords: Authentication, Authorization, Security Architecture, Trust, Ubiquitous Computing